Android Based Mobile Application Development for Web Login Authentication Using Fingerprint Recognition Feature - Yildirim, Nilay; Varol, Asaf (Ieee, 2015)
Many mobile device makers now incorporate biometric security features into their products. And, some device manufacturers now allow application developers to use these features via their software development kits (SDKs). In this study, we utilize fingerprint scanning and recognition technology, a popular biometric security feature, to develop a web login authentication mobile app. Our application uses the Samsung Galaxy S5 fingerprint recognition feature and International Mobile Equipment Identity (IMEI) number to generate single time passwords. Within a limited time frame, the secure passwords can be used to sign in/log in to online user accounts related to government, banking, education, etc. As the production of mobile devices with fingerprint recognition continues to increase, finger print user authentication apps, like the one we introduce in this study, will become a prevalent security measure.
23nd Signal Processing and Communications Applications Conference (SIU) -- MAY 16-19, 2015 -- Inonu Univ, Malatya, TURKEY
Keywords: mobile devices; biometric security; fingerprint recognition; user login